Medical Authority's Trust as Mediator of Risk Perception on Haze Mitigation Efforts - Nurul Aiyuda; Itto Nesyia Nasution (Journal of Psychology and Instruction, 2020)
Haze is a seasonal disaster that continues to recur in several parts of Indonesia. Mitigation as an effort to reduce risk needs to be done to anticipate more losses. Individual risk perceptions in assessing the impact of haze are considered as factors that influence mitigation efforts, however, mitigation is also related to external situations related to individual dependence on the authority that is more authorized in disaster situations, in this case, the medical authority. Trust in medical authorities is considered to mediate the relationship between risk perception and smoke haze mitigation. This study aims to look at the role of trust in medical authorities in helping individuals to perceive risk and seek mitigation. The research sample was 234 affected people, using purposive random sampling. Data were collected on three scales, mitigation scale, risk perception and trust of medical authorities. Research shows that the trust of medical authorities is not able to mediate the relationship between perceived risk and mitigation haze, but risk perception and trust in medical authorities simultaneously contribute to efforts to mitigate the smoke haze in Riau.